Experimental measurements of the hydrodynamic performance and structural loading of the transverse horizontal axis water turbine: Part 2 - McAdam, R; Houlsby, G; Oldfield, M (2013)
This paper is the second of three, which outline the procedures and results for a set of experiments on various configurations of the Transverse Horizontal Axis Water Turbine (THAWT), which is a horizontally orientated variant of the Darrieus cross-flow turbine. Tests were conducted in the combined wind, wave and current tank at Newcastle University on a 0.5m diameter rotor, while the flow depth and velocity were varied over a range of realistic Froude numbers for tidal streams. Various configurations of the device were tested to assess the merits of varied blade pitch, rotor solidity, blockage ratio and truss oriented blades. Experiments were carried out using a speed controlled motor/generator, allowing quasi-steady results to be taken over a range of tip speed ratios. Measurements of power, thrust, blade loading and free surface deformation provide extensive data for future validation of numerical codes and demonstrate the ability of the device to exceed the Lanchester-Betz limit for kinetic efficiency, by exploiting high blockage. This second paper covers the instrumentation and analysis for the structural loading for the parallel bladed variant of the THAWT device. The first paper covers the experimental setup and hydrodynamic performance of the parallel bladed rotor, and the third paper covers both performance and loading of the truss configured THAWT device. © 2013 Elsevier Ltd.